Heritage Animals – Why Not? Anthropocentrism NotwithstandingBaštinske životinje – zašto ne? Usprkos antropocentrizmu - Orlić, Ivona; Marjanić, Suzana (Studia mythologica Slavica, 2018)
<span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">This article discusses the relationship of men towards Istrian cattle (boškarin) through the years. The authors question the problem of treating the animals as objects of natural-cultural heritage. The concepts of Nature and Culture remain anthropocentrically segregated, and this is also reflected in promoting the boškarin as a gastro-phenomenon, which was the dominant feature of the project Boškarin with Potatoes (2012–2014) by the City of Pula, developed as the collaboration with the French town of Villefranche-de-Rouergue, which became the partner city of Pula in 2008. The authors claim that one can only talk about heritage species (especially traditional or autochthonous livestock breeds), but not about heritage animals (the animals in the concept of heritage), and that the anthropology of animals, as defined for instance by socio-cultural anthropologist Barbara Noske, can be – or ought to be – a segment of ethnographic studies of the 21st century.